1998
DOI: 10.1002/(sici)1520-6440(199811)81:11<18::aid-ecjc3>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

VLEGO: A simple two‐handed 3D modeler in a virtual environment

Abstract: Modeling 3D objects in a virtual space has many advantages such as intuitive manipulation. To generate the 3D objects efficiently and precisely, it is useful to introduce optimal assisting methods by software instead of using the special equipment of force feedback displays. On the basis of this idea, we develop a 3D modeler VLEGO in a virtual environment. VLEGO simulates toy blocks, and introduces a number of manipulation assisting methods for virtual object manipulation. The methods have the following three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although precise modelling can be ensured, the constraint-based interactions are too rigid for extensive use. Kiyokawa et al reported a two-handed modelling environment for efficient manipulations in the VR environment [13]. The result was extended to a collaborative VR environment for object creation [8].…”
Section: Previous Workmentioning
confidence: 99%
“…Although precise modelling can be ensured, the constraint-based interactions are too rigid for extensive use. Kiyokawa et al reported a two-handed modelling environment for efficient manipulations in the VR environment [13]. The result was extended to a collaborative VR environment for object creation [8].…”
Section: Previous Workmentioning
confidence: 99%